Impact of sarcopenia on outcome in patients with esophageal resection following neoadjuvant chemotherapy for esophageal cancer. Issue 2 (February 2017) - Paireder, M.; Asari, R.; Kristo, I.; Rieder, E.; Tamandl, D.; Ba-Ssalamah, A.; Schoppmann, S.F.
Abstract: Background: Nutritional status and body composition parameters such as sarcopenia are important risk factors for impaired outcome in patients with esophageal cancer. This study was conducted to evaluate the effect of sarcopenia on long-term outcome after esophageal resection following neoadjuvant treatment. Methods: Skeletal muscle index (SMI) and body composition parameters were measured in patients receiving neoadjuvant treatment for locally advanced esophageal cancer. Endpoints included relapse-free survival (RFS) and overall survival (OS). Results: The study included 130 patients. Sarcopenia was found in 80 patients (61.5%). Patients with squamous-cell cancer (SCC) showed a decreased median SMI of 48 (range 28.4–60.8) cm/m 2 compared with that of patients with adenocarcinoma (AC) of 52 (range 34.4–74.2) cm/m 2, P  < 0.001. The presence of sarcopenia had a significant impact on patient outcome: HR 1.69 (1.04–2.75), P  = 0.036. Median OS was 20.5 (7.36–33.64) versus 52.1 (13.55–90.65) months in sarcopenic and non-sarcopenic patients, respectively. Sarcopenia was identified as an independent risk factor: HR 1.72 (1.049–2.83), P  = 0.032. Conclusion: Our data provide evidence that sarcopenia impacts long-term outcome after esophageal resection in patients who have undergone neoadjuvant therapy. Assessment of the body composition parameter can be a reasonable part of patient selection and may influence treatment methods. Abstract : Sarcopenia, as an independent risk factor, impairs long-term outcome after esophageal resection following neoadjuvant treatment in patients with esophageal cancer.